2019
DOI: 10.1002/jso.25417
|View full text |Cite
|
Sign up to set email alerts
|

Localized synovial sarcoma: A single institutional study of 191 patients with a minimum follow‐up of 5 years for survivors

Abstract: Purpose Factors affecting long‐term outcomes of synovial sarcoma (SS) remain unknown. Here, we aimed to investigate the long‐term oncological outcomes and prognostic factors in a large group of patients with surgically‐treated localized SS. Patients and Methods Between 1980 and 2011, 191 patients (94 males and 97 females) were treated at a single hospital with a minimum follow‐up of 5 years for survivors. The median age was 35 years (range, 3‐80 years), and the median follow‐up period was 83 months (range, 3‐2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…The lung was the most common site of metastasis, and the median time between SS diagnosis and the occurrence of metachronous metastasis was 18 months. Similar data have been reported, with a median interval of 20 months for occurrence of the first metastasis in patients with localized disease [10, 22].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The lung was the most common site of metastasis, and the median time between SS diagnosis and the occurrence of metachronous metastasis was 18 months. Similar data have been reported, with a median interval of 20 months for occurrence of the first metastasis in patients with localized disease [10, 22].…”
Section: Discussionsupporting
confidence: 85%
“…Local relapse was found in 31.3% of the cases, with the median interval between diagnosis and the first relapse being 20.1 months. Outani et al [10] reported a local relapse rate of 12% in their patients after a median interval of 33 months. Bianchi et al [22] reported a local relapse rate of 16%.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from both Surveillance, Epidemiology and End Results (SEER) and NCDB found an overall survival benefit of RT in patients with SaSy undergoing surgery [ 28 , 29 ]. However, two retrospective, single-institution studies demonstrated a significant increase in LRFS with adjuvant RT but no improvement in OS [ 15 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In retrospective analyses, the following are mentioned among factors negatively affecting the prognosis: large primary tumour size, grade 3 tumour, monophasic subtype, male sex, older age at onset, non-extremity location, SS18–SSX1 fusion and resection R1 [ 2 , 5 , 6 , 11 , 13 , 14 , 15 , 16 ]. The strongest evidence exists for an association between primary tumour size and clinical outcome [ 2 , 3 , 5 , 7 , 11 , 15 , 17 , 18 ]. Wide surgical resection combined with perioperative radiation therapy (RT) is the cornerstone in the treatment of patients with localised SaSy.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have identified a number of preoperative prognostic factors in patients with synovial sarcoma, to include sex, age, histological subtype, differentiation, tumor location, tumor size, and the EOD (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). These clinical manifestations were included in the candidate prognostic factors for the current model.…”
Section: Discussionmentioning
confidence: 99%